Bioactive effects of nonthermal argon-oxygen plasma on inorganic bovine bone surface - Wu, Chengzan (Sci Rep, 2020)
As a commonly used bone substitute material in the clinic, inorganic bovine bone has the characteristics of osteoconduction but not osteoinduction. This study aimed to treat inorganic bovine bone using nonthermal argon-oxygen plasma (NTAOP) to obtain greater bioreactivity for enhancing adhesion, proliferation and differentiation of mouse preosteoblast MC3T3-E1 cells. In this study, inorganic bovine bone was activated by NTAOP, and the surface characteristics were analyzed. MC3T3-E1 cells were then seeded onto the surface of inorganic bovine bone. Cell morphology, proliferation and osteogenic differentiation were examined. There was no obvious change in the surface morphology of specimens between the two groups. Regarding the elemental composition of the material, the amount of surface carbon was reduced, whereas oxygen, phosphorus and calcium levels were increased in the NTAOP group. Further studies showed that the NTAOP groups performed better than their untreated counterparts in terms of supporting cell proliferation and differentiation. Inorganic bovine bone treated with NTAOP can promote preosteoblast adhesion, proliferation and differentiation.